Leadership Style and Company Performance of China Service Industry - Yuan, Yue; Mohammad, Farajnezhad (INTI International University, 2024)
Chinese business and government officials increasingly recognize the need for a thorough grasp of company performance. Since the business world has undergone developments that make the prior examination of company performance more difficult, company performance has become a phenomenon of academic inquiry. This quantitative descriptive study investigates the role of leadership style and its relationship to China's service industry; services is the industry with the most significant growth relative to China's GDP in the previous 30 years. As a result, company performance is characterized as an independent variable. The numerous links between ethical, transformational, and transactional leadership are studied as independent variables utilizing relevant literature. In China's service business, essential variations and relationships are represented by an appropriate leadership style to increase company performance. This study employs quantitative analysis. It starts by discussing prior research and presenting the goals of the study, the research questions, and the research hypothesis. Examining past relevant material is used to build the conceptual framework for the research. The technique employed in this investigation will be described. Finally, the research objectives and hypotheses are met using a survey and statistical and descriptive methodologies. The link between company performance and leadership has been established.